K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

24 tháng 10 2022

a) 5x . 52 = 540                               b) 34 . 3x = 326 . 9

=> x .2 = 40                                =>  34 . 3x  = 326 . 32 

=> x     = 40 : 2                           =>  34 . 3x = 328 

=> x     = 20                                => 4 . x = 28

                                                   =>      x = 7 

c) 42x . 4 = 162

=> 42x . 4 = 44

=> 2x . 1 = 4

=> 2x      = 4

=>   x      = 2 

 

24 tháng 10 2022

a) 5x . 52 = 540                               b) 34 . 3x = 326 . 9

=> x .2 = 40                                =>  34 . 3x  = 326 . 32 

=> x     = 40 : 2                           =>  34 . 3x = 328 

=> x     = 20                                => 4 . x = 28

                                                   =>      x = 7 

c) 42x . 4 = 162

=> 42x . 4 = 44

=> 2x . 1 = 4

=> 2x      = 4

=>   x      = 2 

AH
Akai Haruma
Giáo viên
30 tháng 6 2024

Lời giải:

a.

$4(2x-4)+2=18$

$4(2x-4)=16$

$2x-4=16:4=4$

$2x=4+4=8$

$x=8:2$

$x=4$

b.

\(5^3+(18x-65).3=26^2+10\)

$125+3(18x-65)=686$

$3(18x-65)=686-125=561$

$18x-65=561:3=187$

$18x=187+65$

$18x=252$

$x=252:18=14$

c.

\(|x-10|+2^2.5=5^5\)

$|x-10|+20=3125$

$|x-10|=3125-20=3105$

$\Rightarrow x-10=3105$ hoặc $x-10=-3105$

$\Rightarrow x=3115$ hoặc $x=-3095$

d.

\((x-2)^2-2^3.5=104\)

$(x-2)^2-40=104$

$(x-2)^2=104+40=144=12^2=(-12)^2$

$\Rightarrow x-2=12$ hoặc $x-2=-12$

$\Rightarrow x=14$ hoặc $x=-10$

29 tháng 7 2018

a) (2x-1)5 = 2x-1

=> (2x-1)5 - (2x-1) = 0

(2x-1).[(2x-1)4 -1]=0

=> 2x-1 =0 => 2x = 1=> x = 1/2

(2x-1)4 - 1= 0 => (2x-1)4 = 1 = 14 = (-1)4 

                        => 2x-1= 1 => 2x = 2 => x = 1

                            2x -1 = -1 => 2x = 0 => x = 0

KL:...

b) 25x.43 = 169

25x = (42)9:43

25x = 418:43

25x = 415 = (22)15 = 230

=> 5x = 30 => x = 6

c) 3x+1+4.3x = 7.36

3x.3+4.3x = 5013

3x.(3+4) = 5013

3x.7 = 5013

3x = 729 = 36

=> x = 6

12 tháng 8 2018

3x : 3 = 9

3= 9 . 3

3x = 27

3x = 33

=> x = 3

c. 42x - 1 : 22 = 16

    42x - 1 = 16 . 22 

    42x - 1 = 64

    42x - 1 = 43

=> 2x - 1 = 3

=> 2x = 3 + 1

=> 2x = 4

=> x = 2

12 tháng 8 2018

a,3

b,2

c,2

d,5

28 tháng 7 2020

Bài 1 :

a) 1440 : [ 41 - (2x - 5)] = 24.3

=> 1440 : [41 - (2x - 5)] = 16.3

=> 1440 : [41 - (2x - 5)] = 48

=> 41 - (2x - 5) = 1440 : 48 = 30

=> 2x - 5 = 11

=> 2x = 16

=> x = 8

b) 5 . [225 - (x - 10)] - 125 = 0

=> 5 . [225 - (x - 10)] = 125

=> 225 - (x - 10) = 125 : 5 

=> 225 - (x - 10) = 25

=> x - 10 = 200

=> x = 210

Bài 2 :

a) [ 545 - (45 + 4.25)] : 50 - 200 : 250 + 215 : 213

= [ 545 - (45 + 100)] : 50 - 4/5 + 22

= [545 - 145] : 50 - 4/5 + 4

= 400 : 50 - 4/5 + 4 = 8 - 4/5 + 4 =56/5

Mấy câu còn lại tương tự

28 tháng 7 2020

Bài 1.

a, 1440:[41-(2x-5)]=24.3

    1440:[41-(2x-5)]= 16.3

     1440:[41-(2x-5)]=48

      [41-(2x-5)]    =1440:48

      [41-(2x-5)]   = 30

        2x-5         = 41-30

        2x-5        =11

         2x           = 11+5

         2x           = 16

           x          = 16:2

           x          =8

b, 5.[225-(x-10)]-125=0

    5.[225-(x-10)]        =125

       [225-(x-10)]        =125:5

       [225-(x-10)]        = 25

        (x-10)                = 225-25

        (x-10)                = 200

        x                        =200+10

        x                        = 210

Bài 2.

a, [545-(45+4.25)]:50-200:250+215:213

   = [545-(45+100)]:50-200:250+22

   = [545-145]:50- 200:250+4

   = 400:50-200:250+4

   = 8-0,8+4

   = 7,2 + 4

   = 11,4

b, [504-(25.8+70)]:9-15+190

=  [504-(200+70)]:9-15+1

= [504-270]:9-16

= 234:9-16

= 26-16

= 10

c, 5.{26-[3.(5+2.5)+15]:15}

= 5.{26-[3.(5+10)+15]:15}

= 5.{26-[3.15+15]:15}

= 5.{26-[45+15]:15}

= 5.{26-60:15}

= 5.{26-4}

=5.22

= 110

d,[1104-(25.8+40)]:9+316:312

= [1104-(200+40)]:9+34

=[1104-240]:9+34

=864:9+81

=96+81

=177

hok tốt

      

\(a)3-\left(17-x\right)=-24+12\)

\(\Leftrightarrow3-17+x=-12\)
\(\Leftrightarrow-14+x=-12\)

\(\Leftrightarrow x=-12+14=2\)

7 tháng 2 2019

a)  3 - (17 - x) = -24 + 12

=> 3 - 17 + x = -12

=> -14 + x = -12

=> x = -12 + 14

=> x = 2

b) -5 + (16 - x) = 22.3 - 52

=> -5 + 16 - x = 12 - 25

=> 11 - x = -13

=> x = 11 + 13

=> x = 24

c) -26 - (x - 7) = 34 - 92

=> -26 - x + 7 = 81 - 81

=> -19 - x = 0

=> x = -19 - 0

=> x = -19

d) -36 - (4 - x) = 37 + (-5)

=> -36 -  4 + x = 32

=> -40 + x = 32

=> x = 32 + 40

=> x = 72

30 tháng 9 2016

A)                    \(\left(2x+1\right)^2=9^3\)

                    \(\Rightarrow\left(2x+1\right)^2=9^2\times9\)

                    \(\Rightarrow2x+1=81\)

                    \(\Rightarrow2x=81-1\)

                    \(\Rightarrow2x=80\)

                    \(\Leftrightarrow x=40\)

B)                 \(\left(2x+1\right)^3=125^2\)

                      \(\Rightarrow\left(2x+1\right)^3=5^3\)

                      \(\Rightarrow2x+1=5\)

                      \(\Rightarrow2x=5-1\)

                      \(\Leftrightarrow x=2\)

C)                   \(25^2< 5^{x+3}< 25^4\)

                      \(\Leftrightarrow5^4< 5^{x+3}< 5^6\)

                      \(\Leftrightarrow4< x+3< 6\)

                      \(\Rightarrow x+3=5\)

                      \(\Rightarrow x=2\)

D)                   \(x^{15}=x\)

Nếu \(x>1\)thì \(x^{15}>x\)

Vậy \(x=1\)

E)                   \(\left(x-5\right)^4=\left(x-5\right)^6\)

                      \(\Rightarrow\left(x-5\right)^4-\left(x-5\right)^6=0\)

                      \(\Rightarrow\left(x-5\right)\times\left(1^4-1^6\right)=0\)

                     \(\Rightarrow x-5=0\)

                       \(\Leftrightarrow x=5\)

KÍCH MK NHA BẠN

                      

15 tháng 8 2017

a,71.2-6.(2x+5)=10^5:10^3                                                           

    142-6.(2x+5)=10^2

    142-6.(2x+5)=100

           6.(2x+5)=142-100

           6.(2x+5)=42

               2x+5=42:6

               2x+5=7

                  2x=7-5

                  2x=2

                    x=1

Vậy x=1

15 tháng 8 2017

a) 6

b) 81

7 tháng 11 2018

a) \(\text{2(x-51)=2.2^2+20}\)

\(2\left(x-51\right)=2.4+20\)

\(2\left(x-51\right)=28\)

\(x-51=28\div2\)

\(x-51=14\)

\(x=14+51\)

\(\text{b)3.(x+1)-26=541}\)

\(3.\left(x+1\right)=541+26\)

\(3\cdot\left(x+1\right)=567\)

\(x+1=567\div3\)

\(x+1=189\)

\(x=189-1\)

\(x=188\)

\(x=65\)

\(\text{c)4(x-3)=7^2-1^10}\)

\(4\left(x-3\right)=49-1\)

\(4\left(x-3\right)=48\)

\(x-3=48\div4\)

\(x-3=12\)

\(x=12+3\)

\(x=15\)

\(\text{e)2x-138=2^3.3^2}\)

\(2x-138=8\cdot9\)

\(2x-138=72\)

\(2x=72+138\)

\(2x=210\)

\(x=210\div2\)

\(x=105\)

\(\text{f)(x-1)^4=16}\)

\(\left(x-1\right)^4=2^4\)

\(x-1=2\)

\(x=2+1\)

\(x=3\)